2020
DOI: 10.15243/jdmlm.2021.082.2681
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of application of phosphorous and potassium solubilizing multifunctional microbes (Aspergillus costaricaensis and Staphylococcus pasteuri mutants) on maize growth

Abstract: The use of phosphorus and potassium-solubilizing microbes as biofertilizers is an alternative method to increase the availability of phosphorus and potassium in soils. This study aimed to explore the effectiveness of phosphorus (P) and potassium (K)-solubilizing multifunctional microbes (Aspergillus costaricaensis and Staphylococcus pasteuri mutants) on maize growth. The stages of this study consisted of viability test of P and K solubilizing A. costaricaensis and S. pasteuri mutants in peat and effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
2
6
0
1
Order By: Relevance
“…Effectiveness of S. pasteuri and A. costaricaensis on nutrient P (P-total (P2O5) and P-available) (a), nutrient K (K-total (K2O) and K-available) (b) and K-exchangeable (c) of soil in rhizosphere area .77 b Remarks: a Numbers followed by the same letter in the same column show results that are not significantly different based on the DMRT test at a 5% significance level; b P1M0:control with easily soluble P (SP-36) and K (KCl) sources; c P2M0: control with not easily soluble P (rock P) and K (feldspar) sources Stalk dry weight in mutant A. costaricaensis treatment was not significantly different from that in chemical fertilizer treatment, indicating that mutant A. costaricaensis could provide nutrients as much as chemical fertilizer to support stalk dry weight. A similar result was also reported by Sukmadewi et al (2021), who found that treatment with mutant A. costaricaensis combined with rock P and KCl (50% dose) could produce the highest stalk dry weight. Stalk dry weight is the weight of stalk tissue that is not affected by plant water content.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Effectiveness of S. pasteuri and A. costaricaensis on nutrient P (P-total (P2O5) and P-available) (a), nutrient K (K-total (K2O) and K-available) (b) and K-exchangeable (c) of soil in rhizosphere area .77 b Remarks: a Numbers followed by the same letter in the same column show results that are not significantly different based on the DMRT test at a 5% significance level; b P1M0:control with easily soluble P (SP-36) and K (KCl) sources; c P2M0: control with not easily soluble P (rock P) and K (feldspar) sources Stalk dry weight in mutant A. costaricaensis treatment was not significantly different from that in chemical fertilizer treatment, indicating that mutant A. costaricaensis could provide nutrients as much as chemical fertilizer to support stalk dry weight. A similar result was also reported by Sukmadewi et al (2021), who found that treatment with mutant A. costaricaensis combined with rock P and KCl (50% dose) could produce the highest stalk dry weight. Stalk dry weight is the weight of stalk tissue that is not affected by plant water content.…”
Section: Discussionsupporting
confidence: 88%
“…This turgor plant body is influenced by good water regulation in the plant body. Mutant A. costaricaensis can provide sufficient nutrients for plant growth except K. Sukmadewi et al (2021) also reported that mutant A. costaricaensis tended to show the same effects on plant height, stalk, and root dry weight as the easily soluble P and K source control (chemical fertilizer) treatment. According to nutrient uptake data (Table 5), the P nutrient uptake showed no significant difference under mutant A. costaricaensis and chemical fertilizer treatments.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations